KINERJA SEKRETARIAT BADAN PENDAPATAN DAERAH PROVINSI SULAWESI TENGAH DALAM PEMBERIAN TAMBAHAN PENGHASILAN PEGAWAI (TPP) - Apriani, Sitti Hardiyanti; Mangasing, Nasir; Kurnia, Intam (Katalogis, 2020)
The purpose of this study was to determine the Secretariat Performance of the Regional Revenue Agency of Central Sulawesi Province in the Provision of Additional Employee Income (TPP). The foundation of the theory used is the Theory of Agus Dwiyanto (2006) which states that there are four factors in evaluating performance, namely productivity, service quality, responsiveness, responsibility, and accountability. This type of research is Qualitative Descriptive which seeks to interpret and interpret data that is pleasing to the facts, using purposive methods, data cursing and discussion with a qualitative analysis approach to collecting data and materials through observation and interviews with the number of 6 informants. Based on the results of the discussion that the Secretariat Performance of the Regional Revenue of Central Sulawesi Province for Productivity, Service Quality, and Responsiveness has been maximized in the Provision of Additional Employee Income (TPP). However, for responsibility and accountability it has not run optimally in the Provision of Additional Employee Income (TPP) in the Regional Revenue Agency of Central Sulawesi Province due to the discipline of employees who have not gone well.